The essence of parity of educational activity - Krysovatyi, Andriy (Psyhology & society, 2019)
The article is devoted to substantiation of the essence and psycho-didactic conditions of provision the parity of educational activity of teacher and students in joint educational process of modern university. Convincingly proved that to the basic parameters of such parity belongs inter-subjectivity, equality, think activity and dialogicality of interpersonal relations which are actually available in the university area. In the research clearly defined a four-tactfulness of achieving educational parity (understanding – thinking – activity – reflection) first of all depending on self-activity of the personality which also enables eventually four-aspect of equality of learning participants: from semantic and motivational-value harmony of interactions to psychosocial equivalence and the internal acceptance by each the parity as a norm of everyday life.